Ascorbate-reducible b-type cytochrome in the plant plasma membrane - Bérczi, Alajos; Asard, Han (Acta Biologica Szegediensis, 2002)
It has been know for 20 years that the plasma membrane (PM) in plants contains more than one kind of ABSTRACT btype cytochromes. One of them has rather high redox potential (can fully be reduced by ascorbate) and is capable of electron transport through the PM. Three b-type cytochromes have recently been predicted from the full genome of Arabidopsis thaliana. In order to identify and characterize the one located in the PM, first PM vesicles were purified from Arabidopsis leaves, then the PM vesicles were solubilized and the fully ascorbate-reducible b-type cytochrome was partially purified. Redox titration of the partially purified b-type cytochrome revealed the presence of two hemes with redox potentials higher than 100 mV. The major polypeptide band of this fraction on SDS-PAGE was at ~120 kDa. This value is much higher than the apparent molecular mass of either the fully ascorbate-reducible b-type cytochrome purified from Phaseolus hypocotyls or the cyt. b-561 proteins purified from chromaffin granule membranes or the calculated molecular masses for the three polypeptides predicted from the full genome of Arabidopsis.